The Education Inspectorate and the challenges of new technologies (2º part) - Mora Baringo, Vicente (Avances en Supervisión Educativa, 2009)
This second part (first part can be seen in number 9 issue of this magazine) offers a summary and some interpretations on the Law 11/2007 of Electronical Access of Citizens to Public Services, which affects us not only as citicens and civil servants, but, specifically as Inspectors of Education, because of our functions on information, counselling and guidance.
Keywords: new technologies; inspectorate of education; public services